Karya urban kinetik tipografi dalam puisi siber - Ain, R.; Rahamad, M.S. (2010)
In the merge of multimedia literature in Malaysia, the genre which takes the most impact is poetry. It is due to its nature for being simple and easy than any other types of genre in literature. With the increasing growth of multimedia technology, writers are able to get their works published via electronic media, which offers websites purposely created for that particular need. The passion to create extraordinary masterpieces start to become a demand among experimentative writers. There are no more barriers for those who are willing to be more passionate. In order to create extraordinary masterpieces like implementing their work with graphics, musics, effects and turning it into either an animation or a video. This developing kid of work style or urban creation is different compared to the conventional literature. To discuss in depth on this development, this article will look into the poetries that are created with kinetic typography. Poetries in this new perspective can be seen in some personal websites and also in Youtube or social websites.